Gambaran Distress pada Mahasiswa Preklinik Tahun Ketiga Fakultas Kedokteran - Hardisman Hardisman; Dian Pertiwi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: Learning process in medical school is a big stressor for the students. Many researchers have reported higher distress and related psychological health problems in medical students than in general population and non-medical students. This study explored how distress affects Indonesian medical students in FMAU, and its association with academic performance and demographic factors.Method: Cross sectional study was conducted on 185 subjects in the third year medical student of FMAU between April-May 2013. Level of stress was measured using Indonesian version of General Health Questionnaire-12 (GHQ-12), with Liker scale indicator (distress is when the score is >15). Demographic variables such as gender, source of finance, and economic status were assessed in the study. Academic performance was measured by cumulative Grade Point Average (GPA) and last semester GPA. Analyses were done using SPSS.Results: This study identified 35.7% of students were in distress, with average GHQ-12 score 13.42+SD4.97. No association was found between admission pathway, academic performance and distress. However, the study revealed that female students had higher risk of distress (p<0.05).Conclusion: Risk of distress is relatively high in medical students. However, there is no association between demographic factors, academic performance and distress. Further research needs to be conducted to explore risk factors that cause distress of medical students in Indonesian context.